Efeito de fosfito no controle de doenças foliares de trigo in vitro e in sito - Santos, Hellen Aparecida Arantes dos (2008)
The development and grain yield of the crop of wheat are influenced by several factors, among which is the interference caused by pathogens present in crops. Currently, the main tool for controlling these pathogens in crops is the use of constant application of fungicides. However, this practice is causing pathogens resistant to these groups of fungicides used, as well as encouraging the expression of the mutagenic character of these populations. In an attempt to provide more tools to control the diseases of wheat to the farmer, this study aimed to: a) assess the effect of timing of implementation and sources of phosphite and acibenzolar-S-methyl alone and combined with the fungicide pyraclostrobin + epoxiconazole in control the powdery mildew (Blumeria graminis f. sp. tritici) and the leaf rust (Puccinia triticina), b) assess the effect of different rates, sources of phosphite and acibenzolar-S-methyl isolated and associated to the fungicide pyraclostrobin + epoxiconazole in control of the spots brown (Bipolaris sorokiniana) and yellow (Drechslera tritici-repentis); c) and in vitro effect of different concentrations of phosphite and pyraclostrobin + epoxiconazole on the mycelial growth and germination of conidia of Bipolaris sorokiniana. About the control of powdery mildew and rust can be concluded that the phosphites have no effect on these pathogens and do not change their productivity. It is also clear that there is no difference between the different sources of phosphites to control the powdery mildew and leaf rust, which occurs on powdery mildew and leaf rust's only when the phosphite associated with the fungicide is applied. About the control of yellow and brown stains concluded that the dose of 1048 g i.a. ha-1 potassium phosphite reduces the severity of leaf spots and can be used as a tool in the management of leaf spots. In in vitro tests concluded that the phosphites have direct action on Bipolaris sorokiniana.